VD_FINDINFO Jug / 2010 / 3 vom 22. Dezember 2009 - VD Tribunal cantonal (2009)
PARTAGESENS GÉNÉRAL, DIVORCE, PRESTATION DE LIBRE PASSAGE, TRANSACTIONACCORD, INTÉRÊT RÉMUNÉRATOIRE, RENONCIATIONSENS GÉNÉRAL | 142 al. 2 CC, 50 al. 1 LPGA